Liquid-liquid extraction of silver from silver nitrate solution and photograhic waste - exractant selectivity and capacity - Y., Yuliusman; Mat, Hanapi; Othman, Norasikin (1998)
In recent years, there has been increasing interest to recover precious metals from industrial wastes such as to recover silver from photographic and semiconductor wastes. Several methods have been used for this purpose such electrolysis, ion exchange, precipitation and solvent extraction. However, solvent extraction has been recognized to be an effective method to extract metals especially in the case of metal concentration is very low. This purpose can be achieved by using an appropriate extractant specific to the target metals. Since the nature of the wastes containing a wide range of metals and concentrations, the selection of extractants that provide high selectivity and capacity towards the target metals are very crucial. Besides that there is very little information in the literature dealing with extractant selectivity and capacity involving mixed metal system. In this work, several silver extractants as reported in the literature such as dithizon, cyanex 272, cyanex 302, cyanex 471X, DEPHA, benzoylacetone, DOPP and 8-hydroxyquinoline were studied. It was found that the extent of extraction depends on the type of extractants and their concentrations, pH and, metal concentration and composition in the sample. It was also found that for all extractant used the selectivity and capacity depend so much on pH except for dithizon. The percentage of extraction of silver using diction is about 95% and independence of pH.